Multi input intervention model for evaluating the impact of the asian crisis and terrorist attacks on tourist arrivals - Lee, Muhammad Hisyam; Suhartono, Suhartono; Sanugi, Bahrom (Faculty of Science, 2010)
The objective of this research is to study the impact of the Asian financial crisis and terrorist attacks Bali on the number of tourist arrivals by using a multi input intervention model. The focus is on the development of a model that could be used to explain the magnitude and periodic impacts of the Asian financial crisis since July 1997 and terrorist attacks referring to the Bali bombings on October 12th 2002 and October 1st 2005, respectively. Monthly data comprising the number of tourist arrivals in Indonesia via Soekarno-Hatta airport are used as the data for this case study. The results show that the Asian financial crisis and Bali bombings yield negative impacts on the number of tourist arrivals to Indonesia via Soekarno-Hatta airport. Generally, the Asian financial crisis gives a negative permanent impact after seven month delay. The first and second Bali bombings also yield negative impacts which were temporary effect after six and twelve months delay respectively. In addition, this research also discusses how to assess the effect of an intervention in transformation data